Experience With a Research and Innovation Office to Support Laboratory Medicine and Pathology Research. (11th September 2019) - Beinborn, Julie; Saling, Kenneth; Reed, Katelyn; Ibrahim, Mohamed; Feldman, Andrew
Abstract: Objectives: Translational research in laboratory medicine and pathology is transforming health care based on recent quantum advances in omics technologies, computational science, and precision medicine. However, high-volume clinical settings where this research may be most effective often have significant constraints on faculty time that challenge productivity. The objective of this study was to assess our experience with a new resource designed to address this challenge. Methods: In September 2016, we established the Research and Innovation Office (RIO) in the Department of Laboratory Medicine and Pathology, Mayo Clinic–Rochester. The goal was to provide infrastructure to unburden faculty from performing administrative, organizational, and operational tasks related to research. Over 30 months, we solicited faculty input into desired services, conducted surveys on utility and ease of use, and tracked metrics, including faculty participation, numbers of projects, and publications. Results: Faculty members were highly satisfied with the range of services, ease of use, and service-oriented approach of RIO. Initial services included project organization, institutional process support (eg, IRB protocol management), biospecimen requests and handling, and data management. Based on early feedback, patient consenting, budget support, and manuscript assistance were added as additional services. Total RIO staff increased from 6 to 10 during in the first 30 months. Over this time, 97 of 160 faculty members (60%) utilized RIO services in over 1, 000 discrete project requests. Annual departmental publications increased by 50% during this time. Conclusion: Faculty time is a critical element for translational research productivity in laboratory medicine and pathology departments. Numerous tasks previously performed by faculty could be managed effectively by a team of research facilitators that unburdened constraints on research time and led to high levels of faculty engagement, satisfaction, and productivity. This model may promote advances in transformative laboratory medicine and pathology research in high-volume clinical settings.